Model teacher grit dalam mendukung kemandirian siswa penyandang disabilitas di sekolah inklusi - Muallifah; Ilhamuddin (Mediapsi, 2024)
The physically, mentally and intellectually limited conditions of students with disabilities result in them being more dependent on the environment around them. Therefore, a teaching model and mentoring by diligent teachers (teacher grit) are needed to help students. This research aims to find a teacher grit model in teaching and mentoring students with disabilities. The method used in this research is a qualitative research approach with a phenomenological model. The research respondents were two male and three female teachers with at least two years of teaching in inclusive schools. The research results show that the teacher grit model was obtained through factors supporting two aspects of grit: Consistency of Interest, including goal setting, initiative, self-care, and optimism. Meanwhile, the Perseverance of effort aspect includes self-acceptance, emotional bonding, social and psychological support, interpersonal communication, and proactive coping. Looking at the teacher grit model, it confirms that it is important for teachers to have perseverance and consistency to support the independence of students with disabilities.